ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN PADA PELAKU USAHA MIKRO DI KOTA BATAM - yuliadi, yuliadi; Br Purba, Neni Marlina; Natalia, Erni Yanti (LPPM Universitas Putera Batam, 2024)
This research was conducted with the aim of analyzing factors that can influence the income of micro business actors in Batam City. The population in this study were all micro businesses registered with the Sekupang Batam cooperative body. Meanwhile, samples were taken using the Slovin formula. Hypothesis testing in this research was carried out using instrument tests consisting of validity tests and reliability tests, then descriptive analysis tests. The classic assumption test consists of the normality test, multicollinearity test and heteroscedasticity test. Apart from that, it also uses multiple linear regression tests, simultaneous tests (F test), partial tests (t test) and determination tests (R2 test). The results of this research show that partially business capital has a significant effect on business income, while business scale has a negative but not significant effect on business income. Meanwhile, simultaneously business capital and business scale have a significant influence on business income.